A REVIEW OF SOLAR FARM DEVELOPMENT IN MALAYSIA FROM THE PERSPECTIVE OF LAND ADMINISTRATION - Sahid, Mohd Shahrizan; Suratman, Robiah; Ali, Hishamuddin Mohd (International Journal of Psychosocial Rehabilitation, 2020)
The increase of energy demand due to globalisation and population growth has made solar energy as one of the green and sustainable alternative energy in the world. This energy has a great potential worldwide as the solar radiation can be accessed globally. Promoting this energy however has inevitably forced this new industry to face some drawbacks particularly related to land matters. Therefore, this paper reviews the solar farm development, policy evolution, and current legislation practices that govern the country’s land administration. The review of the existing procedures in some states that have developed solar farms shows that there is no uniformity in the legal framework used in developing solar farms as there are different methods and approaches of land approval used by the State Authority. Therefore, the discussion in this paper is used to determine the direction a legal framework development that serves as a foundation to standardize the land approval for solar farm development in Malaysia following the sustainable land use management. This leads to a strong motivation and interest for the development and use of renewable energy technology especially in the country.